Online Exam System to Improve Student Learning Quality in State Vocational School 5 Tangerang City - Aris Martono; Arsi Yulianjani; Dewi Immaniar Desrianti (CCIT Journal, 2020)
The aim of this research is designing an online examination system at SMK Negeri 5 Kota Tangerang. This time, the system used in assessing exam results is done by correcting each question of each student's answers. It is not only increasing the operational costs of schools, but also the risk that leaked exam questions very vulnerable. As well as scheduling the exam must consider the limited number of rooms and require a lot of time. The method of collecting datais used observation, interview and literature study. And the system analysis method is used to determine the number of functional and non functional requirements. The design method uses Unified Modeling Language (UML) with the MySQL database system. This visual paradigm function is to make use-case diagrams, sequence diagrams, and activity diagrams and class diagrams. The use-case diagram of this system consists of use case diagrams of students, teachers, and teachers admin system and PHP programming language, for writing program listings using Dreamweaverand implementing the system. By using online examination system the quality of student learning will be improved, lowering school administration costs and preventing question leakage and exam scheduling to become more flexible.